Prevention and combating measures against doping in the Republic of Moldova (One Health & Risk Management, 2023)
Introduction. Anabolic androgenic steroids are synthetic hormones designed to enhance the body's ability to produce muscle tissue. Despite their therapeutic effects, these steroids come with a range of side effects, which vary based on each user's sensitivity and especially on the doses used. Typically, the use of these substances without a medical prescription, in uncontrolled doses, or in amounts exceeding therapeutic levels, is considered a highly risky practice. In recent times, there has been a surge in the demand for these substances among athletes and individuals aiming to increase muscle mass or achieve short-term sports performance. In the Republic of Moldova, the issue of the unauthorized use of anabolic substances and the illegal trade of such substances has evolved over time and become a significant concern for public health.Material and methods. For the purpose of researching the unauthorized use of anabolic steroids and the illicit trafficking of anabolic substances in the Republic of Moldova, an examination has been conducted over time, beginning in 2013, specifically focusing on the illegal trade of these substances through online channels. This involved compiling information on the commercial names, active substances, and prices for each medication offered in these online listings.Results. The issue of unauthorized use and illegal trafficking of anabolic steroids has been a long-standing problem, posing significant health risks. A notable concern regarding the illicit trafficking of anabolic substances in the Republic of Moldova is the sale of these substances through the internet, without adhering to legal requirements. The prominent problem is that anabolic steroids, including nandrolone, metenolone, oxymetholone, testosterone, etc., are readily available on the website 999.md without the need for a valid medical prescription or compliance with other legal regulations, posing a major risk to public health. This underscores the urgent need to implement measures to combat this phenomenon and safeguard the health and safety of the population. Without intervention, the situation may escalate, leading to an increase in the prevalence of unauthorized use and a higher number of individuals exposed to health risks.Conclusions. The unauthorized use and abuse of anabolic steroids constitute a significant problem that adversely affects individuals and society as a whole. The existence of a developed online market for the trading of anabolic steroids and the associated illicit traffic is a major concern. Some immediate effects of addressing this issue may include reducing the availability of anabolic steroids on the market, disrupting criminal networks, and discouraging the unauthorized use of these substances. However, long-term effects, such as reducing the overall rate of anabolic steroid use, completely eliminating illegal trafficking, and improving public health, may necessitate more time for adequate observation and evaluation. Without effective measures to combat the illegal trade in anabolic steroids, the illicit trade could persist, enabling unauthorized access to these substances. This could create a vicious circle, leading to dire consequences for public health and social stability.Note: The study was carried out with the support of the Moldovan-Turkish bilateral research and innovation project 23.80013.0807.4TR "Common Actions in Anti-Doping Research through Piloting of Innovative Interventions in Education".